ANALISIS KONDISI INTERNAL DAN EKSTERNAL USAHA KECIL DI KOTA PALEMBANG IMPLIKASINYA TERHADAP PENCAPAIAN HASIL USAHA - M Syahirman Yusi (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
The aim this study is to obtain the empirical evidence about internal and external conditions in small scale enterprises in Palembang. Primary data was collected through survey technique from 100 samples, respondents taken by random sampling method and was analysed by Two Stage Least Square (TSLS). Through analysis showed that in agregate all of variables had a positive influence not only in first hypothesis, but also in second and third, it means all of the hypothesis were not rejected.